Adhesions in repeat caesarean sections: prevalence, predictive factors, and surgical outcomes - Jain, Aastha; Chandra, Ramesh; Agarwal, Manaswi; Mansoori, Sabiya; Manohari (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Adhesion formation is a common sequela of repeat caesarean sections (CS), associated with increased surgical complexity and morbidity. This study aimed to identify maternal and surgical predictors of adhesion formation and to assess its intraoperative and postoperative consequences. Methods: This cross-sectional cohort study was conducted at Sawai Mansingh Medical College, Jaipur, from June to December 2024. A total of 100 women undergoing repeat CS were included. Data on maternal demographics, surgical history, intraoperative findings, and postoperative outcomes were collected. Adhesions were graded as mild, moderate, or dense. Statistical analysis was performed using statistical package for the social sciences (SPSS) version 26, with p value <0.05 considered statistically significant. Results: Adhesions were present in 35% of cases 15% mild, 11% moderate, and 9% dense. Significant predictors of adhesion formation included higher body mass index (BMI) (p=0.003), greater number of previous CS (p=0.0212), and higher parity. Adhesions were significantly associated with increased operative time (mean 60.56±8.46 minutes for dense adhesions), greater hemoglobin drop (1.10±0.25 g/dl versus 0.65±0.26 g/dl, p<0.001), higher rates of intraoperative blood transfusion (66.7% versus 7.7%, p<0.001), and visceral injury (44.4% versus 0%, p<0.001). Duration of hospital stay did not differ significantly between groups. Conclusions: Adhesion formation in repeat CS is significantly associated with maternal risk factors and adversely impacts surgical outcomes. Anticipating adhesions through risk assessment and applying meticulous surgical techniques are essential to minimize complications.